2020
DOI: 10.1088/1361-6382/abccdd
|View full text |Cite
|
Sign up to set email alerts
|

Beam propagation simulations for LISA in the presence of telescope aberrations

Abstract: Accurate simulation of the propagation of light between the spacecraft of the laser interferometer space antenna (LISA) gravitational wave observatory will be a vital tool in determining the optical design of the telescopes used in the constellation. In this work, we examine the methods available for numerical simulation of this propagation, and consider the effect of an aberrated transmitting telescope (Tx) on the light collected by the receiving telescope (Rx). Propagation software has been developed using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Recently, Ming et al made an analytical analysis to confirm that large defocus and small coma is helpful to make the stationary point close to the central axis and reduce the phase noise [9]. Based on Bessel function expressions, Vinet et al built a far-field optical model and proposed an extreme requirement of the wavefront aberration of the telescope [10]. Kenny et al analyzed the first 11 Zernike aberrations and revealed only even index terms will contribute to the far-field phase [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ming et al made an analytical analysis to confirm that large defocus and small coma is helpful to make the stationary point close to the central axis and reduce the phase noise [9]. Based on Bessel function expressions, Vinet et al built a far-field optical model and proposed an extreme requirement of the wavefront aberration of the telescope [10]. Kenny et al analyzed the first 11 Zernike aberrations and revealed only even index terms will contribute to the far-field phase [11].…”
Section: Introductionmentioning
confidence: 99%
“…[11] The numerical simulation is used to describe the effect of an aberrated transmitting telescope on the light collected by the receiving telescope with Zernike modes. [12] Via calculations of the wavefront aberrations in the far field, an end-to-end investigation of the measurement noise due to the interaction between the telescope jitters and wavefront aberrations is reported in Ref. [13].…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis of TTL noise induced by WFE begins in section 2 as a first order expansion in SC jitter components coupling to the received field's phase gradient, yielding two TTL coupling components to two jitter degrees of freedom. This first order expansion in jitter allows for actual recovery of expected TTL noise as a function of receiving SC location, in contrast to methodologies of prior studies [18,19] where the TTL is defined more as a statistic over the entire map. We discuss how gradients are obtained via a Hermite-Gaussian (HG) modal decomposition based propagation of an approximation in our initial beam, and the limitations of this approximation.…”
Section: Introductionmentioning
confidence: 99%
“…Having verified the accuracy of these expansions, the maps associated with polynomial terms show only some Zernikes within WFE, specified in section 4, couple significantly to TTL noise. We can then neglect a significant number of unimportant terms in the expansions, further speeding up this fast modeling technique without a loss of accuracy, allowing for more extensive simulations than those of prior studies [18,19].…”
Section: Introductionmentioning
confidence: 99%